Pengaruh Model Pembelajaran Project Based Learning terhadap Keaktifan Siswa Kelas X pada Materi Teknologi Informasi dan Komunikasi di SMA Negeri 1 Pinogaluman - Firmansyah Butolo; Arip Mulyanto; Ihsanulfu'ad Suwandi (Transbahasa, 2026)
Learning under the Merdeka Curriculum is student-centered and therefore requires active student participation in the teaching and learning process. However, in practice, students tend to be passive and show limited interaction, resulting in low learning engagement and, consequently, low learning outcomes in Class X at State Senior High School 1 Pinogaluman. This study aims to examine the effect of the Project-Based Learning (PjBL) model in improving student engagement in Informatics, specifically on the topic of Information and Communication Technology. This research employed a quantitative approach using a quasi-experimental method. The subjects consisted of 30 students divided into two groups: an experimental group and a control group, each comprising 15 students. The findings indicate that the Project-Based Learning model has a positive impact on student engagement. This is evidenced by the higher average score of the experimental group, which was taught using PjBL, achieving 67,33%, compared to the control group, which achieved an average score of 51,33% without the implementation of PjBL. The use of the Project-Based Learning model encourages students to be more actively involved in learning, while students in the control group tend to be more passive. Based on the significance test results, the Project-Based Learning model has a statistically significant effect on student engagement.